2016
DOI: 10.1161/circimaging.115.004316
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of 18 F-Fluorodeoxyglucose Uptake in Postischemic Myocardium by Simultaneous Positron Emission Tomography/Magnetic Resonance Imaging as a Prognostic Marker of Functional Outcome

Abstract: Background The immune system orchestrates the repair of infarcted myocardium. Imaging of the cellular inflammatory response by 18F-FDG PET/MRI in the heart has been demonstrated in preclinical and clinical studies. However, the clinical relevance of post-MI 18F-FDG uptake in the heart has not been elucidated. The objective of this study was to explore the value of 18F-FDG-PET/MRI in patients after AMI as a biosignal for left ventricular functional outcome. Methods and Results We prospectively enrolled 49 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 45 publications
1
62
0
Order By: Relevance
“…In experimental models of AMI, the application of 18 fluorodeoxyglucose ( 18 FDG) PET in combination with MRI further improved localization of infiltration of metabolically active leukocytes in experimental models 98 , with cellular imaging studies supporting these conclusions 99 . Clinical studies have demonstrated similar findings, which provide the capacity to quantify metabolic activity in the myocardium after infarction 100 , monitor continued disease activity, and might also provide a prognostic marker of functional outcome 101 .…”
Section: Acute Myocardial Infarctionmentioning
confidence: 86%
“…In experimental models of AMI, the application of 18 fluorodeoxyglucose ( 18 FDG) PET in combination with MRI further improved localization of infiltration of metabolically active leukocytes in experimental models 98 , with cellular imaging studies supporting these conclusions 99 . Clinical studies have demonstrated similar findings, which provide the capacity to quantify metabolic activity in the myocardium after infarction 100 , monitor continued disease activity, and might also provide a prognostic marker of functional outcome 101 .…”
Section: Acute Myocardial Infarctionmentioning
confidence: 86%
“…Unlike mice, inflamed ischemic tissue in humans is often interspersed with normal surviving myocytes, creating a heterogeneous distribution that can confound clinical interpretation. To explore whether 18 F-FDG uptake can be used clinically post MI, Rischpler, et al 56 prospectively evaluated 49 patients with STEMI using 18 F-FDG PET/MRI 5 days after PCI with a follow-up cardiac MRI after 6-9 months. The mean standardized uptake value (SUV mean) of 18 F-FDG was detected in transmural scars and was associated with left ventricular dysfunction independent of infarct size measured by late gadolinium enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…PET-CT is known to be less specific as inflammatory cells will also cause increased FDG avidity, most commonly in the context of infection. However, increased uptake has also been reported in postischemic or infarcted tissue [27][28][29], atherosclerosis [30], physiological papillary muscle [31], hypertrophied papillary muscle [32], and postoperative contexts [32]. To our knowledge, there are no reported cases of chronic mitral regurgitation due to prolapse being a cause of increased FDG avidity.…”
Section: Discussionmentioning
confidence: 90%